2018
DOI: 10.1158/1078-0432.ccr-17-3004
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Therapeutic Targeting to Overcome Venetoclax Resistance in Aggressive B-cell Lymphomas

Abstract: B-cell lymphoma-2 (BCL-2), an antiapoptotic protein often dysregulated in B-cell lymphomas, promotes cell survival and provides protection from stress. A recent phase I first-in-human study of the BCL-2 inhibitor venetoclax in non-Hodgkin lymphoma showed an overall response rate of 44%. These promising clinical results prompted our examination of the biological effects and mechanism of action underlying venetoclax activity in aggressive B-cell lymphoma, including mantle cell lymphoma (MCL) and diffuse large B-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 43 publications
(50 reference statements)
4
53
0
Order By: Relevance
“…6 Pham and colleagues recently reported that venetoclax treatment activates the DNA damage response in lymphoma cells, though the mechanism is unknown. 28 In agreement, we show that inhibition of Wee1 or RRM1 in combination with venetoclax cooperatively induce DNA damage in AML cells.…”
Section: Discussionsupporting
confidence: 82%
“…6 Pham and colleagues recently reported that venetoclax treatment activates the DNA damage response in lymphoma cells, though the mechanism is unknown. 28 In agreement, we show that inhibition of Wee1 or RRM1 in combination with venetoclax cooperatively induce DNA damage in AML cells.…”
Section: Discussionsupporting
confidence: 82%
“…As an example, one study showed that either short-or long-term exposure of B-cell lymphoma cell lines (MCL and DLBCL) to venetoclax led to the development of venetoclax resistance due to a reduction in PTEN expression (a negative regulator of the PI3K/AKT activation pathway). 36 Our RPPA analysis from three IR cell lines showed a significant decrease in PTEN expression with enhanced expression of activated AKT (p-AKT) and downstream activation of mTOR signaling, suggesting the critical role of PI3K signaling in survival of acquired IR-DLBCLs ( Figure 2C).…”
Section: Discussionmentioning
confidence: 92%
“…Our group has been involved in various clinical trials with ibrutinib, acalabrutinib, venetoclax (a Bcl2 inhibitor), and their combinations with anti‐CD20 monoclonal antibodies (mAb), rituximab, or with obinutuzumab. Furthermore, we are characterizing ibrutinib, acalabrutinib, and venetoclax‐refractory MCL and championing the CAR‐T cell clinical trials (Zuma‐2) in MCL in the United States.…”
Section: Advances In the Treatment Of MCLmentioning
confidence: 99%